2016
DOI: 10.3748/wjg.v22.i39.8658
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided techniques for diagnosing pancreatic mass lesions: Can we do better?

Abstract: The diagnostic approach to a possible pancreatic mass lesion relies first upon various non-invasive imaging modalities, including computed tomography, ultrasound, and magnetic resonance imaging techniques. Once a suspect lesion has been identified, tissue acquisition for characterization of the lesion is often paramount in developing an individualized therapeutic approach. Given the high prevalence and mortality associated with pancreatic cancer, an ideal approach to diagnosing pancreatic mass lesions would be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 101 publications
1
26
0
3
Order By: Relevance
“…In cases of pancreatic body and tail lesions, no significant difference among the three types of needle has been found . FNA needles have different echogenicity . In a multicenter study evaluating 10 different EUS needles, the polymeric‐coated needle showed the highest echogenicity …”
Section: Interventional Eus: New Tools New (And Old) Applicationsmentioning
confidence: 97%
See 1 more Smart Citation
“…In cases of pancreatic body and tail lesions, no significant difference among the three types of needle has been found . FNA needles have different echogenicity . In a multicenter study evaluating 10 different EUS needles, the polymeric‐coated needle showed the highest echogenicity …”
Section: Interventional Eus: New Tools New (And Old) Applicationsmentioning
confidence: 97%
“…47 FNA needles have different echogenicity. [49][50][51] In a multicenter study evaluating 10 different EUS needles, the polymeric-coated needle showed the highest echogenicity. 52 Consistent tissue core acquisition with EUS-guided biopsy has recently been achieved through the development of new side-and end-cutting EUS needles, with different mechanisms, calibers and design.…”
Section: Fusion Imagingmentioning
confidence: 99%
“…Recent papers have shown that evidence‐based techniques to increase the diagnostic yield during EUS‐FNA of pancreatic masses include the use of general anesthesia, smaller (22‐G or 25‐G) needles for transduodenal FNA and 19‐G or core biopsy needles if histology is required. Moreover, it is suggested to use the suction and the ‘fanning’ technique or to perform seven needle passes …”
Section: Endoscopic Tips For Diagnostic Alliancementioning
confidence: 99%
“…In centers providing special requirements such as highly trained endoscopists proficient in EUS-guided biopsy approaches, equipment and on-site cytology will reach specificity of up to 96% and sensitivity of up to 87% as reported by recent systematic meta-analyses [ 7 ], [ 8 ]. However, specificity for the diagnosis of malignancy reported in the literature ranges between 80 and 100%, while sensitivity is much more variable with an overall low and variable negative predictive value (33-85%) [ 9 ]. Many factors can impact the diagnostic yield of EUS-FNA including the experience of both the endosonographer and cytologist, availability of on-site cytology, and the inherent limitations of the procedure to identify cytomorphologic features characteristic of well-differentiated cancer, in particular in the setting of chronic pancreatitis (CP).…”
Section: Introductionmentioning
confidence: 99%